The frequency and structure of comorbid infections in patients with spondyloarthritis (preliminary own data) - M. M. Baranova; N. V. Muravyeva; B. S. Belov (Медицинский совет, 2021)
Introduction. Data on the frequency of comorbid infections (CI) in patients with spondyloarthritis (SpA) are few and contradictory. Objective. The aim of the study was to study the frequency and structure of CI in the inpatient population of SpA patients in the course of a one-moment retrospective study.Subjects and methods. The study included 205 patients with SPA: 119 men, 86 women, the age of patients was 39.02 ± 12.2 years, the duration of the disease was 129.3 ± 104.3 months. Ankylosing spondylitis was diagnosed in 133 patients, psoriatic arthritis in 55, spondyloarthritis associated with Crohn’s disease – in 1, undifferentiated spondyloarthritis – in 16. Most patients, along with nonsteroidal anti-inflammatory drugs, received glucocorticoids, basic anti-inflammatory drugs, and biological drugs. Patients were interviewed by a research doctor with the completion of a unified questionnaire, additional data were obtained from medical documentation.Results. 20% of patients reported more frequent CI development after the SpA debut. 28.7% of patients reported a more severe course of previously observed CI. Temporary discontinuation of therapy due to the development of CI occurred in 25.4% of patients. Exacerbation of SpA after CI was diagnosed in 40% of patients. In general, the leading place in the structure of CI was occupied by infections of the respiratory tract and ENT-organs, the second place belonged to herpes-viral infections. Serious CI accounted for 6.8% of all cases of CI. In SpA patients receiving immunosuppressive therapy, there was an increase in the frequency of acute nasopharyngitis, sinusitis, acute bronchitis, pneumonia and herpes-viral infections. However, cases of CI have also been reported in patients who have never received immuno-suppressive drugs.Conclusion. The data obtained indicate the important of the problem of CI in SpA. Further studies are needed on large samples of patients in order to find significant risk factors for CI, study their relationship with clinical characteristics and influence on the course of SpA.